The diversity of developmental paths among youth athletes: A 3-year longitudinal study of Norwegian handball players - Thue Bjørndal, C.; Ronglan, L. T.; Andersen, S. S. (Talent Development & Excellence, 2016)
This longitudinal study examines pathways leading to adult elite sport in Norwegian handball. The study cohort - a sample of Norwegian female handball players (n=33) selected to youth national team activities - was followed over three years (2013-2015). Some participants reached the elite level (n=21); others reached the near-elite level (=6) or non-elite level (n=6). The findings show that elite players in Norwegian handball are more involved with youth national team activities than nonelite players. There was more variation in the amount of international experience within the elite and near-elite groups than between the groups; the pathways to the adult elite level were variable between athletes. The findings are discussed in relation to the characteristics of the particular organisational context of Norwegian handball.